IFPRI key facts series: Key facts sheet on agricultural commercialization - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
Four out of five Malawian households engage in some crop production. Rural households are most likely to farm – nine out of ten do so. However, even in towns and cities, almost one-third of urban households engage in some farming. However, only 60 percent of households engaged in farming reported selling any of what they harvested – while almost 70 percent of farming households in the Central region sell some of their harvest, just under 60 percent in the Northern region and 45 percent in the Southern region do so. The commercial importance of the crops produced by farming households differ: Maize, sorghum, finger millet, pearl millet, and cassava predominantly are grown for own consumption. Soyabean, tobacco, cotton, and Irish potato are produced primarily for sale. Rice, groundnut, pigeonpea, bean/cowpea, and sweet potato are all important for subsistence, while also sold. Trends are seen of increased shares of farming households both producing and selling several of these crops. Farming households in the Southern region are much less likely to sell the maize they produce than households in the other two regions. A slightly greater share of the maize consumed by Malawian households is purchased rather than own-produced. While this is the case for urban households, as expected, it also holds for rural households. Greatest reliance on the market for maize by rural households occurs in the months up to January. For the period October 1999 to February 2020, about 70 percent of all maize consumed by Malawian households, whether in rural communities or in urban centers, was obtained from the market.